Probing nuclear effects with neutrino-induced charged-current neutral pion production - Coplowe, D; Altinok, O; Ahmad Dar, Z; Barr, G; Lu, X; Wark, D; Weber, A; Minerva Collaboration (American Physical Society, 2020)
We study neutrino-induced charged-current (CC) π 0 production on carbon nuclei using events with fully imaged final-state proton-π 0 systems. Novel use of final-state correlations based on transverse kinematic imbalance enable the first measurements of the struck nucleon’s Fermi motion, of the intranuclear momentum transfer (IMT) dynamics, and of the final-state hadronic momentum configuration in neutrino pion production. Event distributions are presented for i) the momenta of neutrino-struck neutrons below the Fermi surface, ii) the direction of missing transverse momentum characterizing the strength of IMT, and iii) proton-pion momentum imbalance with respect to the lepton scattering plane. The observed Fermi motion and IMT strength are compared to the previous MINERνA measurement of neutrino CC quasielastic-like production. The measured shapes and absolute rates of these distributions, as well as the cross-section asymmetries show tensions with predictions from current neutrino generator models.